Analysis of MinC Reveals Two Independent Domains Involved in Interaction with MinD and FtsZ - Hu, Zonglin (American Society for Microbiology, 2000)
In Escherichia coli FtsZ assembles into a Z ring at midcell while assembly at polar sites is prevented by the min system. MinC, a component of this system, is an inhibitor of FtsZ assembly that is positioned within the cell by interaction with MinDE. In this study we found that MinC consists of two functional domains connected by a short linker. When fused to MalE the N-terminal domain is able to inhibit cell division and prevent FtsZ assembly in vitro. The C-terminal domain interacts with MinD, and expression in wild-type cells as a MalE fusion disrupts min function, resulting in a minicell phenotype. We also find that MinC is an oligomer, probably a dimer. Although the C-terminal domain is clearly sufficient for oligomerization, the N-terminal domain also promotes oligomerization. These results demonstrate that MinC consists of two independently functioning domains: an N-terminal domain capable of inhibiting FtsZ assembly and a C-terminal domain responsible for localization of MinC through interaction with MinD. The fusion of these two independent domains is required to achieve topological regulation of Z ring assembly.